2017
DOI: 10.1007/s13311-017-0558-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Repair in Multiple Sclerosis: Outcomes for Phase II Clinical Trials

Abstract: Multiple Sclerosis (MS) pathology is complex and includes inflammatory processes, neurodegeneration, and demyelination. While multiple drugs have been developed to tackle MS-related inflammation, to date there is scant evidence regarding which therapeutic approach, if any, could be used to reverse demyelination, foster tissue repair, and thus positively impact on chronic disability. Here, we reviewed the current structural and functional markers (magnetic resonance imaging, positron emission tomography, optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 95 publications
1
18
0
Order By: Relevance
“…What explains the variation in chronic immune responses between individuals? In conjunction with additional imaging tools for assessment of demyelination and remyelination, neurodegeneration and synaptic loss [151][152][153][154] , the impact of chronic neuroinflammation and its modulation in the CNS can now be studied directly.…”
Section: {H1} Conclusionmentioning
confidence: 99%
“…What explains the variation in chronic immune responses between individuals? In conjunction with additional imaging tools for assessment of demyelination and remyelination, neurodegeneration and synaptic loss [151][152][153][154] , the impact of chronic neuroinflammation and its modulation in the CNS can now be studied directly.…”
Section: {H1} Conclusionmentioning
confidence: 99%
“…[25][26][27] As a less expensive, more convenient, and more accessible tool than magnetic resonance imaging (MRI) to measure axonal injury, these results have motivated pursuit of OCT as an alternative clinical trial outcome. 10,11 Important to establishing the concept of subclinical axonal injury were the longitudinal OCT studies that followed the initial cross-sectional observations. These studies have consistently demonstrated a loss of approximately 2 microns per year in mean global pRNFL in MS non-ON eyes, in comparison to 0.25 microns per year from aging alone in healthy controls.…”
Section: Subclinical Axonal Lossmentioning
confidence: 99%
“…It became clear that this device could be applied to study other optic neuropathies and neurological conditions, such as MS. One of the first articles on OCT and MS, which appeared in 1999 by Parisi et al, demonstrated reduced retinal nerve fiber layer (RNFL) thickness in 14 patients with MS. 9 By 2005, there were still only a small number of articles using OCT to study multiple sclerosis or optic neuritis, but over 1,500 articles have now been published on these topics (PubMed). OCT measures have been included as endpoints in clinical trials of disease-modifying and remyelination agents, 10,11 Keywords ► optical coherence tomography ► multiple sclerosis ► neuromyelitis optica…”
mentioning
confidence: 99%
“…During recent years, OCT measures have been proven as appropriate outcome measures in multiple sclerosis clinical trials, often in combination with LCVA and other clinical measures [77]. In particular, optic neuritis has been proposed as a unique clinical model to study the potential of neuroprotective and neurodegenerative therapies.…”
Section: Clinical Relevance Of Optical Coherence Tomography Findings mentioning
confidence: 99%